Práxis pedagógica unitária: do conto musical “Pedro e o lobo” à avaliação reflexiva - Bittencourt, Eugênio Pacelli Leal (2005)
The thesis Pedagogical praxis unitary: from musical tale "Peter and the wolf" to reflective evaluation resulted the project Pedro and the Wolf: from reflective evaluation to resignification the pedagogical practice, executed to change the practices of classroom space. The school evaluation is a fascinating topic, but theorizing, research, criticism, seem to have a little contributed to overcome the pedagogy exam which propagates in educational institutions. Many factors contribute to the process does not suffer the wanted revolution. This work supports the otherness of the whole school practice, at the same time. As an epistemological snnipet, begins the criticism of the fragmented logic processes and subjugated condition of the students to the teacher to the unitary model proposition, with practice in real space and time. The model includes tracks, suggestions and promises of public and academic works, about what should be done to change practices. Fundamental was the concept of reflective teacher, that the researcher incarnated as methodological approach. It was created a proper way to study, reflective research development, whose contributions were the design of the reflective practitioner, phenomenology, critical theory and social interactionism. The main technique was the pedagogical intervention; the main protocol, the field diary; the goal, the (re) creation of routines, processes, strategies and teaching tools. We sought to the analisys – the double meaning of the term: decomposition (to tell the experience) and interpretation – the (re)totalization proposal planning, teaching-learning and assessment, in which the student was subjected. The context was the Integrated Educational Center, basic education school of the Federal University of Pará, in which the researcher worked as a teacher of sciences, in a 5th grade class. The construction of the data extended from December 2000 to September 2002. In the pre-intervention during the last two months of 2000, the researcher observed the routine of 4th grade class that the following year would work. At the end, he interviewed 50% of teachers and class. In the intervention phase, in addition to the pedagogical action, other techniques and instruments were: photography; the logbook; the portfolio. It lasted throughout the school year 2001, with the right to strike a hundred days "on the way". After interviews were carried out with a third of the students, six women teachers and one men teacher of the class, to set common points and differentiated between experiences. The research had two horizons. The first, which focused on the reinterpretation of the planning of education (co-operative), the teaching-learning and evaluation (reflective), was reached. It was reinvention time, with the dismantling of the old ways and the construction of the new . The second, which focused on the development of processes, techniques , tools and forms of analysis to enjoy reflectively the quality of teaching and student actions at the level of self and peer assessment, has been achieved in part. A school year was not enough to carry the precept that review is to compare (up what had been developing target). The gap was thus interpreted: the (re)totalization processes, in reframing the evaluative act, in the exercise of the condition of the subject by the learner, time for reflective teaching and learning is the training cycles, instead the serialize regimen. The study confirmed the thesis defended. In interviews, most of the students of the 5th grade did not remember as was evaluated in Science. Who remembered, made reticent way, with quotes from other experiences than those experienced in Praxis Unitary. As for teaching activities and teacher-student relationship, privileged aspects in the modified logic, the memories were rich in detail. No memories and recollections confirm the value of the emphasis on teaching and learning, rather than the verification of what is taught, in cracking what is "tradition" in schools. Other conclusions: the unitary model favors interdisciplinarity between school subjects and the very nature of science; planning of education (with the student body) and evaluation (with all evaluating all) lose their original character and terminal that they have and are converted into shares and educational operations, with a tendency to internalize as ways of thinking. The research concludes that the "secret" to overcome the problems of fragmented logic of process, is, philosophically, in changing conception of science and, pragmatically, the otherness of the relationship between learners and teachers.